STUDIES ON THE RELATIONSHIP BETWEEN THE PATHOGENICITY OF PARACOCCIDIOIDES-BRASILIENSIS IN MICE AND ITS GROWTH-RATE UNDER DIFFERENT OXYGEN ATMOSPHERES - Sano, A.; Miyaji, M.; Nishimura, K.; Defranco, M. F. (Kluwer Academic Publ, 1991)
We performed comparative studies of the pathogenicity of six strains of Paracoccidioides brasiliensis (Bt-9, Bt-4, Pb-9, Pb-18, Bt-7 and B-1183) for young adult male ddY mice and growth rate of each strain under different oxygen atmospheres (aerobic, micro-aerobic and anaerobic atmospheres) at 37-degrees-C. 10(6) units of yeast cells were intravenously injected into each mouse. The pathogenicity of each isolate was determined by a scoring system based on organ culture and histopathological findings. The growth rates under different oxygen atmospheres were determined by a scoring system in which 300 fungal units per strain were counted. The strain Bt-9 showed the greatest pathogenicity, followed by Bt-4. Pb-9 and Pb-18 had on intermediate rank of pathogenicity. Bt-7 and B-1183 were the least pathogenic of the strains tested. Except for strain Bt-7 all strains showed an excellent growth under an aerobic atmosphere. Bt-4 and Bt-9 also showed excellent growth under a micro-aerobic atmosphere, followed by Pb-9, whereas the growth of Pb-18, Bt-7 and B-1183 was limited. There was a correlation between the growth rate under a micro-aerobic atmosphere and the pathogenicity of a strain. The growth rate of P. brasiliensis under a micro-aerobic atmosphere strongly correlated to its pathogenicity.
Keywords: GROWTH RATE; MICRO-AEROBIC ATMOSPHERE; PARACOCCIDIOIDES-BRASILIENSIS; PATHOGENICITY